Menyama Braya Sebagai Upaya Membangun Kerukunan Hidup Umat Beragama di Bali - Paskalis Nyoman Widastra (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2008)
Living in harmony with one another is one of the main problems in our modern society. To promote such a humane life, especialy in this mobile and multicultural society, should be the effort of everybody. People of every kind of social life and religious background are expected to offer their contribution for bonum commune (common good), particularly in treating others as neighbours. In fact, every religion and culture has inherently such value which enculturates its members to treat others as their brothers and/or sis- ters. This paper highlights one of the Balinese traditional values, the so-called 'menyama braya way of thinking and of behaving, which means 'living together as brother and sister'. This kind of local genius - although menyama braya sounds out of date - seems to be needed in our more and more intolerant society. Basically menyama braya (brotherhood or sisterhood), which springs out of the heart of Balinese religious culture that has enculturated its people for centuries, promotes harmony in the society, where everybody could feel at home and lives comfortably. The writer encourages everybody of good will to elaborate again and again this human value, primarily in and for Balinese context and also within our multicutural society of today.